A Qualitative Analysis of the Influence of the 2020 Economic Recession on Marketing Decisions: A Cross-Organizational Study - Soji Alabi; Tayo Popoola; Moshood-Abiola Arogundade (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
The study examined the impact of the 2020 economic recession on the marketing strategies of several firms in Nigeria. A qualitative research approach was employed, and data was collected from twenty (20) individuals across four sectors: telecommunications, real estate, media and entertainment, and banking. Data was collected utilising a semi-structured interview framework. A majority of the responders, 13 (65%), were females, with a mean age of roughly 33 years. Findings indicated that businesses had justifications for making a variety of marketing decisions. In addition to a substantial decrease in budgetary allocation, organisations implemented modifications in transitioning to digital advertising platforms, enhancing digital business operations, aligning organisational processes with technology, and embracing a customer-centric advertising approach. The findings suggest that while digital advertising offers cost efficiencies, companies should anticipate rising platform costs and algorithm changes by diversifying their marketing strategy.